SUKUK RATING: MATURITY, SUKUK STRUCTURE AND GUARANTEE WITH PROFITABILITY AS MODERATION - Rafiatul Ulum; Muhammad Husni Mubarok (Universitas Airlangga, 2024)
Introduction: The development of corporate sukuk in Indonesia increases every year, which is why a credible sukuk rating is very necessary. Sukuk is a sharia investment instrument with minimal risk. This research aims to determine the factors that influence sukuk ratings from non-financial factors such as maturity, sukuk structure and guarantee with profitability as moderation through 130 samples of corporate sukuk issued in 2018-2022. Method: The method used is descriptive analysis, Ordinal Logistic Regression and Moderate Analysis Regression with SPSS 25 software. Results: The research results show that maturity and structure sukuk have a significant negative effect, the guarantee has a significant positive effect on sukuk rating. Profitability is not able to moderate the influence of maturity on sukuk rating, profitability weakens the influence of the sukuk structure on the sukuk rating and profitability strengthens the influence of guarantee on the sukuk rating on the sukuk rating. Conclusion and suggestion: Therefore, potential investors must pay attention to the sukuk ranking and the company's level of profitability before deciding to invest. Companies must pay attention to the company's economic and non-economic conditions in order to minimize the risk of default.